An Investigation of Canva’s Impact on Narrative Text Writing Skill - Wahdania, Wahdania; Permana, Dio Resta; Angraini, Nike (Indo-MathEdu Intellectuals Journal, 2024)
Writing skills are a difficult challenge for many EFL students who have little exposure to real language outside the classroom. Therefore, this research aims to explore the influence of using Canva in teaching narrative text writing to LTI Indo Global Mandiri Middle School students in Palembang and their perceptions of using Canva. The research design used was a quasi-experimental design. The sample for this research was classes VIII.A and VIII.B which consisted of 20 students from class VIII.A and 19 students from class VIII.B. The research design used in this research is a quasi-experimental design. The sampling technique used is purposive sampling, namely selecting certain individuals who are believed to represent the population studied. Data collection was carried out by giving a pre-test and post-test, then analyzed using a t-test (paired sample t-test and independent sample t-test) with the help of the SPSS v.23 program. The results of this research show that the p-value from the paired sample t test of 0.000 is less than 0.05, which means there is a significant increase in students' writing skills after being taught using the Canva application. The results of this research show that the use of the Canva application as a learning media can improve the ability to write narrative texts for class VIII students at SMP LTI Indo Global Mandiri Palembang.